Sagittal plane kinematics of a mobile-bearing unicompartmental knee arthroplasty at 10 years: a comparative in vivo fluoroscopic analysis. - Price, A; Rees, J; Beard, D; Gill, R; Dodd, C; Murray, D (2004)
This study compares in vivo sagittal plane kinematics of the Oxford mobile-bearing unicompartmental knee arthroplasty (UKA) at 1 and 10 years' postsurgery (10 knees) with a fixed-bearing total knee arthroplasty (TKA) (5 knees) and the normal knee (5 knees), using dynamic fluoroscopic measurement of the patellar tendon angle. The Oxford UKA preserved normal changes in patellar tendon angle with flexion, and this was maintained at 10 years. In contrast, an abnormal pattern was seen with the TKA. The results suggest that a normal pattern of sagittal plane knee kinematics exists following Oxford medial UKA and imply that anterior cruciate ligament function is maintained in the long term.